Penentuan Tempat Lokasi Usaha Baru Menggunakan Simple Multi Attribute Rating Technique Method - Reflan Nuari (PT. Tech Cart Press, 2024)
Determining the location to establish a new business is a critical stage in the business planning process. The right decision in choosing a location can have a significant impact on the success and continuity of the business. The location of a new business has many factors to consider, but there are some problems that entrepreneurs often face in this process. One is the limitation of accurate and up-to-date information about local market conditions, infrastructure, and business regulations in the location under consideration. The lack of comprehensive data can make decision-making less accurate and potentially lead to errors in assessing market potential as well as environmental and social risks. Determining the location of a new business using Simple Multi Attribute Rating Technique (SMART) involves a series of structured and measurable steps. Application of the SMART method to identify and assess various attributes that are relevant and have an impact on business success, as well as to investigate the advantages of the SMART method in providing an objective and measurable approach to the decision-making process, as well as to test the effectiveness of this method in reducing risk and increasing the chances of success in establishing new ventures. The data from alternative ranking provides recommendations for determining the location of new businesses with the results of rank 1 with a value of 0.7583 obtained by CH Village, rank 2 with a value of 0.6167 obtained by ST Village, and rank 3 with a value of 0.4625 obtained by DR Village.